2021
DOI: 10.3390/tropicalmed6030139
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Potential HIV Transmission Risk in Recent Anal Intercourse Events among Men Who Have Sex with Men and Transgender Women in Bali, Indonesia

Abstract: In recent years, prevalence of Human Immunodeficiency Virus (HIV) has increased substantially in Bali, Indonesia, in men who have sex with men (MSM) and transgender women, known locally as ‘waria’. There are limited behavioural data in this population. We conducted a behavioural survey of MSM/waria in Bali in March–April 2018. Respondents were primarily recruited by HIV outreach workers. Respondents reported details about anal intercourse events with their last male/waria romantic partner and/or last male/wari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
0
3
1
Order By: Relevance
“…Our results indicate that even in casual relationships, in which condom use tends to be higher compared to those involving steady partners, there is still a significant percentage of MSM who do not use condoms (50.8%) consistently, increasing the level of exposure to HIV and other STIs. This prevalence was higher than in other studies, such as that by Ulrich et al 20 , conducted in Peru, where 20% of MSM that had more than one partner reported condomless anal intercourse (CLAI) with all of them, or Bavinton et al 21 , where the prevalence was 30.4% for casual partners in MSM in Bali, Indonesia.…”
Section: Discussioncontrasting
confidence: 56%
“…Our results indicate that even in casual relationships, in which condom use tends to be higher compared to those involving steady partners, there is still a significant percentage of MSM who do not use condoms (50.8%) consistently, increasing the level of exposure to HIV and other STIs. This prevalence was higher than in other studies, such as that by Ulrich et al 20 , conducted in Peru, where 20% of MSM that had more than one partner reported condomless anal intercourse (CLAI) with all of them, or Bavinton et al 21 , where the prevalence was 30.4% for casual partners in MSM in Bali, Indonesia.…”
Section: Discussioncontrasting
confidence: 56%
“…This is due to the lack of awareness amongst them when it comes to protection and information on contraception. Furthermore, in some parts of Asia, contraception may be difficult to access [45,59,75], expensive [39], and in some cases prove to be a taboo [7]. This can make it challenging for women to use protection consistently.…”
Section: Sexualmentioning
confidence: 99%
“…In addition, the wide use of online social networks to meet sexual partners facilitates sexual risk behavior in this group [ 15 ]. This creates an environment that limits disclosure of risk practices (e.g., multiple sex partners [ 16 ], sexualized drug use (SDU) [ 17 ]), and missed opportunities to access HIV prevention and other sexual health programs for MSM [ 18 ]. This becomes more problematic in the context of low levels of HIV viral suppression, inadequate knowledge of HIV prevention and treatment, and poor coverage of HIV PrEP [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the socioecological and HIV-related epidemiological and behavioral contexts for MSM in Indonesia [ 20 ], there has been little research on their combined contribution to shaping overall HIV risk. Most studies of MSM in Indonesia have focused on describing individual behaviors as drivers of risk, such as condomless anal intercourse (CAI) as a driver of HIV risk, the role of HIV status in influencing risk behaviors, and the effect of HIV knowledge on unsafe sex [ 16 , 21 , 22 ]. Some studies have begun to recognize the contribution of social and structural factors to HIV risk [ 23 ], but have not directly assessed their links with individual risk behaviors and sexual practices.…”
Section: Introductionmentioning
confidence: 99%